Gratian the theologian - Wei, John C. (Studies in medieval and early modern canon law, 2016)
Gratian the author and biblical exegete -- Gratian and his book(s) -- The Bible -- Gratian the penitential theologian -- The practice and theory of penance -- Gratian on penance -- Critiquing and correcting the scholastics -- From penitential theology to the canon law of magic -- Gratian, a theologian of the sacraments and liturgy? -- Gratian, a sacramental theologian? -- Gratian, a liturgist?